Evidence for improved survival with bevacizumab treatment in recurrent high-grade gliomas: a retrospective study with (“pseudo-randomized”) treatment allocation by the health insurance provider - Hofmann, Susanne (J Neurooncol, 2020)
INTRODUCTION: Despite a large number of trials, the role of bevacizumab (BEV) in the treatment of recurrent high-grade gliomas is still controversial. Evidence regarding an effect on overall survival in this context is ultimately inconclusive. At the Department of Radiation Oncology at Erlangen, Germany we treated a large cohort of patients with recurrent gliomas where bevacizumab use was determined exclusively by the health care provider’s approval of reimbursement. METHODS: 61 patients (between 06/2008 and 01/2014) with recurrent high-grade gliomas had reimbursement requests for BEV sent to their health insurance. 37 patients out of 61 (60.7%) had their requests approved and therefore received bevacizumab (BEV-arm) as part of their treatment. The remaining 24 (39.3%) patients received standard therapy without bevacizumab (non-BEV-arm). Survival endpoints were defined with reference to the first BEV request to the health insurance provider. RESULTS: Median overall survival (OS) for the whole cohort was 7.0 months. OS was significantly better for BEV vs. Non-BEV patients (median, 10.3 vs. 4.2 months, logrank p = 0.023). There was an increased BEV benefit in cases of higher-order recurrences (first order recurrence BEV vs. Non-BEV, 12.5 vs. 10.2 months, p = 0.578) (second or higher order of recurrence, 9.9 vs. 2.6 months, p = 0.010). On multivariate analysis for overall survival the prognostic impact of bevacizumab (HR = 0.43, p = 0.034) remained significant. CONCLUSION: Our results suggest an influence of BEV on overall survival in a heavily pretreated patient population suffering from high-grade gliomas with BEV benefit being greatest in case of second or later recurrence.